Viral tropism for the testis and sexual transmission - Wang, Fei; Zhang, Jing; Wang, Yu; Chen, Yongmei; Han, Daishu (Frontiers in Immunology, 2022)
The mammalian testis adopts an immunoprivileged environment to protect male germ cells from adverse autoimmune reaction. The testicular immunoprivileged status can be also hijacked by various microbial pathogens as a sanctuary to escape systemic immune surveillance. In particular, several viruses have a tropism for the testis. To overcome the immunoprivileged status and mount an effective local defense against invading viruses, testicular cells are well equipped with innate antiviral machinery. However, several viruses may persist an elongated duration in the testis and disrupt the local immune homeostasis, thereby impairing testicular functions and male fertility. Moreover, the viruses in the testis, as well as other organs of the male reproductive system, can shed to the semen, thus allowing sexual transmission to partners. Viral infection in the testis, which can impair male fertility and lead to sexual transmission, is a serious concern in research on known and on new emerging viruses. To provide references for our scientific peers, this article reviews research achievements and suggests future research focuses in the field.